2020
DOI: 10.1519/jsc.0000000000003399
|View full text |Cite|
|
Sign up to set email alerts
|

Cycling Performance Enhancement After Drop Jumps May Be Attributed to Postactivation Potentiation and Increased Anaerobic Capacity

Abstract: de Poli, RAB, Boullosa, DA, Malta, ES, Behm, D, Lopes, VHF, Barbieri, FA, and Zagatto, AM. Cycling performance enhancement after drop jumps may be attributed to postactivation potentiation and increased anaerobic capacity. J Strength Cond Res 34(9): 2465–2475, 2020—The study aimed to investigate the effects of drop jumps (DJs) on supramaximal cycling performance, anaerobic capacity (AC), electromyography, and fatigue. Thirty-eight recreational cyclists participated into 3 independent studies. In study 1 (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 38 publications
2
43
0
1
Order By: Relevance
“…We add that oxidative metabolism continues to dominate ATP provision during exercise at an intensity >100% of MAP and this is supported by fat metabolism (probably intramuscular triacylglycerol) via the ß‐oxidation pathway. This high oxidative energetic contribution is similar to that reported by de Poli 36 during exercise at the same relative intensity (i.e., 115% of maximal aerobic power and 63% of oxidative contribution).…”
Section: Discussionsupporting
confidence: 88%
“…We add that oxidative metabolism continues to dominate ATP provision during exercise at an intensity >100% of MAP and this is supported by fat metabolism (probably intramuscular triacylglycerol) via the ß‐oxidation pathway. This high oxidative energetic contribution is similar to that reported by de Poli 36 during exercise at the same relative intensity (i.e., 115% of maximal aerobic power and 63% of oxidative contribution).…”
Section: Discussionsupporting
confidence: 88%
“…< 5 minutes) potentiation responses have also been observed in some studies with both resistance [16,17] and ballistic [13] exercises. More importantly, several studies have suggested the necessity of individualized approaches as the generalization of findings is often not valid for individual responses in the same studies [6,[16][17][18]. In this regard, if we consider our recent taxonomy proposal [7], which highlights the necessity of better identifying the main factors of PAPE as CA, the verification test, and population, it may be suggested that other potential moderators (e.g.…”
Section: Pape Factors and Their Moderatorsmentioning
confidence: 99%
“…In this respect, it is still to be determined if more specific stimuli for endurance athletes (e.g. prolonged submaximal exercise) [51] would elicit greater PAPE than highintensity brief efforts [6,32,50] or a combination of both stimuli [41]. Importantly, this may be related to the physiological profile of the athletes (e.g.…”
Section: Warm-upmentioning
confidence: 99%
See 2 more Smart Citations